2005
DOI: 10.1111/j.1743-6109.2005.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Sexual Concerns: Data Analysis from a Help–Line

Abstract: Purpose To report female sexual problems and concerns, as presented by women calling a help–line, and to evaluate women’s help–seeking behavior regarding sexual matters. Materials and Methods The study included all telephone calls from women who called for sexual concerns to a help–line dedicated to sexual problems during a 5–year period. During the call, the counselor addresses demographic characteristics of the caller, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
(48 reference statements)
6
30
2
1
Order By: Relevance
“…In many studies, it has been shown that the most common sexual problems are lack of desire, lubrication and arousal, anorgasmia, and dyspareunia [1,6,9,21,29]. In the present study, vaginismus and avoidance were found at higher rates, whereas anorgasmia was at a lower rate.…”
Section: Discussionsupporting
confidence: 50%
“…In many studies, it has been shown that the most common sexual problems are lack of desire, lubrication and arousal, anorgasmia, and dyspareunia [1,6,9,21,29]. In the present study, vaginismus and avoidance were found at higher rates, whereas anorgasmia was at a lower rate.…”
Section: Discussionsupporting
confidence: 50%
“…This finding is not in accordance with data from other studies and epidemiological research, which indicate DD and OD as the most frequently reported difficulties by women (8,15,34,35). This finding is not in accordance with data from other studies and epidemiological research, which indicate DD and OD as the most frequently reported difficulties by women (8,15,34,35).…”
Section: Discussioncontrasting
confidence: 93%
“…Despite this, relatively little scientific information is available, especially regarding helpline services for women (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Despite this, relatively little scientific information is available, especially regarding helpline services for women (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Although men and women both experience a range of sexual concerns, many previous researchers have consistently found that women report sexual concerns more frequently than men (Laumann et al;Sobczak, 2009a;Zakhari). For females, desire and orgasmic disorders have been found to be the most common complaints; for males, erectile dysfunction and premature ejaculation are among the most common complaints (Babineau & Schwartz, 1977;Papaharitou et al, 2005;Santtila, Sandnabba, & Jern, 2009;Sobczak, 2009aSobczak, , 2009bWiesmeier & Forsythe, 1982;Zakhari). If the definition of sexual dysfunction is broadened to include sexual functioning concerns, or sexual health problems that do not meet diagnostic criteria for a diagnosable dysfunction, prevalence estimates may be even higher.…”
Section: Sexual Health and Dysfunction Prevalencementioning
confidence: 95%